2022
DOI: 10.2478/jvetres-2022-0004
|View full text |Cite
|
Sign up to set email alerts
|

Development of a real-time TaqMan PCR assay for the detection of porcine circovirus 4

Abstract: Introduction Porcine circovirus 4 (PCV4) was first discovered in 2019 in a herd of pigs with porcine respiratory disease, dermatitis and nephropathy syndrome in Hunan Province, China. It has subsequently been detected in other provinces and in South Korea. In consideration of the potential of the virus to cause an epidemic, rapid, sensitive, and specific detection of PCV4 is needed, as is the facilitation of further epidemiological research through elucidation of the whole genome of PCV4. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…For clinical evaluation of the newly developed tqPCR assay and investigation of prevalence and co-infection status of PCVs in Korean pig farms, 1476 clinical samples collected from 198 pig farms were tested using the tqPCR and each monoplex qPCR assays. The results were in 100% agreement with those of previously reported monoplex qPCR assays for PCV2, PCV3, and PCV4 (Kim et al, 2017;Chen et al, 2022), regardless of the tested sample type, with a κ value (95% CI) of 1 (1.00∼1.00), were 100% concordant with the tqPCR assay (Table 3). (39/198), respectively (Fig.…”
Section: Clinical Evaluation Of Tqpcr Assaysupporting
confidence: 86%
See 3 more Smart Citations
“…For clinical evaluation of the newly developed tqPCR assay and investigation of prevalence and co-infection status of PCVs in Korean pig farms, 1476 clinical samples collected from 198 pig farms were tested using the tqPCR and each monoplex qPCR assays. The results were in 100% agreement with those of previously reported monoplex qPCR assays for PCV2, PCV3, and PCV4 (Kim et al, 2017;Chen et al, 2022), regardless of the tested sample type, with a κ value (95% CI) of 1 (1.00∼1.00), were 100% concordant with the tqPCR assay (Table 3). (39/198), respectively (Fig.…”
Section: Clinical Evaluation Of Tqpcr Assaysupporting
confidence: 86%
“…1∼3). The sensitivity of the developed tqPCR assay was <10 copies/μL for PCV2, PCV3, and PCV4, which was comparable to that of previously reported duplex PCR assay for PCV2 and PCV3 (Kim et al, 2017) and like those of SYBR Green (Zhang et al, 2020a;Hou et al, 2021) and TaqMan qPCR assays (Chen et al, 2022) for PCV4. To assess the intraassay repeatability and inter-assay reproducibility of the tqPCR, three different concentrations of each standard DNA were tested in triplicate on six different runs performed by two different operators on different days (Bustin et al, 2009).…”
Section: Clinical Evaluation Of Tqpcr Assaysupporting
confidence: 81%
See 2 more Smart Citations
“…A TaqMan rtPCR assay was recently developed to help detecting porcine circovirus 4. Results shown that the established method was specific for PCV-4; it recorded 99.6% efficiency and detection limit of 2.2 × 10 DNA copies [ 11 ]. Liu et al developed a sensitive assay using droplet digital PCR (ddPCR) to detect PCV-3.…”
Section: Introductionmentioning
confidence: 99%